1985
DOI: 10.1104/pp.77.3.591
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Localization of the Phytoalexin Glyceollin I in Relation to Fungal Hyphae in Soybean Roots Infected with Phytophthora megasperma f. sp. glycinea

Abstract: A radioimmunoassay specific for glyceollin I was used to quantitate this phytoalexin in roots of soybean (Glycine max [L.] Merr. cv Harosoy 63) after infection with zoospores of either race 1 (incompatible) or race 3 (compatible) of Phytophthora megasperma Drechs. f. sp. glycinea Kuan and Erwin. The sensitivity of the radioimmunoassay and an inmmunofluorescent stain for hyphae permitted quantitation of phytoalexin and localization of the fungus in alternate serial cryotome sections from the same root. The inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
70
0
3

Year Published

1989
1989
2011
2011

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(79 citation statements)
references
References 21 publications
6
70
0
3
Order By: Relevance
“…Hahn et al (9) observed significant glyceollin accumulation in resistant roots at 2 h after inoculation but not until 12 h in susceptible roots. Bonhoff et al (2) detected threefold greater CHS activity in resistant than in susceptible roots at 9 h after inoculation with zoospores.…”
Section: Induction Of Mrna In Pathogen Inoculated Leavesmentioning
confidence: 99%
“…Hahn et al (9) observed significant glyceollin accumulation in resistant roots at 2 h after inoculation but not until 12 h in susceptible roots. Bonhoff et al (2) detected threefold greater CHS activity in resistant than in susceptible roots at 9 h after inoculation with zoospores.…”
Section: Induction Of Mrna In Pathogen Inoculated Leavesmentioning
confidence: 99%
“…Similar metabolic engineering will be also applicable for the agricultural field to confer disease resistance in crop plants, for instance, against soil-borne pathogens like Fusarium spp. (Zhang and Smith, 1983;Hahn et al, 1985). Further use of SfN8DT genes for the generation of wood biomass with increased resistance for rot fungi can also be expected in sustainability sciences.…”
Section: Table II Production Of Prenylated Flavonoids In Transgenicmentioning
confidence: 99%
“…CHS and STS are closely related plant-specific polyketide synthases that are key enzymes in the biosynthesis of flavonoid and stilbene phytoalexins (Rolfs and Kindl, 1984;Lanz et al, 1991;Schroder et al, 1993). The toxic effect of flavonoid (Skipp and Bailey, 1977;Hahn et al, 1985;Delserone et al, 1992) and stilbene phytoalexins (Ilart, 1981;Dercks and Creasy, 1989) on pathogenic fungi i! ; well documented.…”
Section: Lnhibition Of Mycelial Growthmentioning
confidence: 99%